2018
DOI: 10.1595/205651318x15302623075041
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Phenol using in situ Generated Hydrogen Peroxide Combined with Fenton’s Process

Abstract: Oxidative destruction of organic compounds in water streams could significantly reduce environmental effects associated with discharging waste. We report the development of a process to oxidise phenol in aqueous solutions, a model for waste stream contaminants, using Fenton’s reactions combined with in situ synthesised hydrogen peroxide (H2O2). Bifunctional palladium-iron supported catalysts, where Pd is responsible for H2O2 synthesis while Fe ensures the production of reactive oxygen species required for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Numerous studies have investigated the efficacy of H 2 O 2 generated in situ over Pd−Fe based catalysts utilising a range of hydrogen sources such as formic acid, hydroxylamine and hydrazine . Indeed Underhill et al . have recently reported that superior rates of phenol conversion can be achieved from H 2 O 2 generated in situ from molecular H 2 and O 2 , compared to preformed H 2 O 2 , with this superiority ascribed to the absence of stabilising compounds, such as phosphoric acid and acetanilide, found in commercial H 2 O 2…”
Section: Application Of H2o2 As An In Situ Oxidantmentioning
confidence: 99%
“…Numerous studies have investigated the efficacy of H 2 O 2 generated in situ over Pd−Fe based catalysts utilising a range of hydrogen sources such as formic acid, hydroxylamine and hydrazine . Indeed Underhill et al . have recently reported that superior rates of phenol conversion can be achieved from H 2 O 2 generated in situ from molecular H 2 and O 2 , compared to preformed H 2 O 2 , with this superiority ascribed to the absence of stabilising compounds, such as phosphoric acid and acetanilide, found in commercial H 2 O 2…”
Section: Application Of H2o2 As An In Situ Oxidantmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a versatile, environmentally friendly oxidant that finds applications as a bleaching agent in the pulp and textile industry, 1 the treatment of waste streams 2,3 and is finding growing use in the production of both commodity and fine chemicals. With the demand from the chemical sector in particular driven by the growing need for both propylene oxide, via the integrated HPPO process, 4,5 and cyclohexanone oxime, a key intermediate in the production of Nylon-6.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] The ability of H2O2 to destroy chemicals found in waste streams such as thiocyanate, nitrate and hypochlorite is well known. [12,13] In recent years increasing focus has been placed on the treatment of organic pollutants from wastewater streams with numerous studies reporting the efficacy of H2O2 used in conjunction with Fenton's reagent, [14][15][16][17][18] with the photo-Fenton process, in particular, representing an interesting alternative approach. [19][20][21] Annual global production of H2O2 is growing at a rate of approximately 4 % year on year with demand forecast to exceed 5 million tons per annum by 2020.…”
Section: Introductionmentioning
confidence: 99%